Faut-il former les enseignants afin qu’ils cherchent à diminuer les émotions négatives de leurs élèves ou qu’ils leur apprennent à renforcer leurs émotions positives ? - Philippe A. Genoud; Gabriel Kappeler; Philippe Gay (Recherches en Éducation)
This article focuses on the impact that positive and negative emotions can have on students' school motivation. The role played by their self-confidence is also taken into account. The results (from a sample of 1 371 students in their last year of compulsory schooling, collected through a self-reported questionnaire measuring socio-affective attitudes towards learning) confirm a strong link between positive emotions and school motivation. Negative emotions have a much lower and indirect influence (through the self-confidence) in the tested model. While one-shot measures only suggest a sense of causality between the pleasure of learning and investment, the establishment of a virtuous circle between these dimensions is quite plausible. Contrarily to the usual practice that advocates prioritizing anxiety in the classroom, our research raises the interest of focusing more on positive emotions, because it is these that have direct and stranger effects on students' school motivation. This change of focus should be extended to the training of teachers in order to better equip these professionals to develop and maintain positive emotions in the school. The ultimate goal is to intervene in a direct and targeted way on students’ school motivation.